Application of knowledge gained from the coordination of partial movements in breasstroke and butterfly swimming for the development of technical training - Hahn, A.; Krug, T. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
The aim of this study was to biomechanically analyse the coordination of partial movements in breaststroke and butterfly within different load ranges. By obtaining objective information about the coordination of partial movements, improvements in technical training could be achieved. For technique training a relatively complex procedure has been developed and experimentally tested. The profiles of velocity in breaststroke and butterfly swimming has provided important findings about the criteria for effectiveness of swimming techniques. This has allowed technical models of coordination in these swimming styles to be considerably improved. The results concerning the specificity of coordination in load ranges such as basic endurance and competition specific endurance, as well as under conditions of exhaustion, are informative. This knowledge is the basis of the present development of a specific training technique for breaststroke and butterfly. The measuring capability of speedography has allowed us to pinpoint problem areas and focus on these during training.